Robust H∞ Control for Singular Time-Delay Systems via Parameterized Lyapunov Functional Approach. (27th November 2014) - Liu, Li-li; Wu, Bao-wei; Wang, Yue-E
Abstract : A new version of delay-dependent bounded real lemma for singular systems with state delay is established by parameterized Lyapunov-Krasovskii functional approach. In order to avoid generating nonconvex problem formulations in control design, a strategy that introduces slack matrices and decouples the system matrices from the Lyapunov-Krasovskii parameter matrices is used. Examples are provided to demonstrate that the results in this paper are less conservative than the existing corresponding ones in the literature.